2008
DOI: 10.1007/s12011-008-8180-1
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Levels in Different Causes of Death: Diagnostic Efficacy in Drowning

Abstract: Trace element determination can be applied in forensic medicine to diagnose the cause of death. Drowning is the second leading cause of death from unintentional injury. Despite the many diagnostic methods used, the post-mortem diagnosis of drowning continues to be one of the most difficult in forensic pathology. Strontium is a highly sensitive marker of water aspiration in a liquid medium rich in this metal. The aims of this study were to confirm the diagnostic value of strontium in cases of drowning compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(35 reference statements)
1
10
1
Order By: Relevance
“…These authors confirmed the usefulness of cardiac blood (or postmortem serum from cardiac blood) Sr levels in diagnosing seawater and freshwater drownings, together with circumstantial data and morphological findings, especially in cases which have been in the water for less than 72 h [116][117][118][119][120][121][122][123].…”
Section: Electrolytessupporting
confidence: 57%
See 2 more Smart Citations
“…These authors confirmed the usefulness of cardiac blood (or postmortem serum from cardiac blood) Sr levels in diagnosing seawater and freshwater drownings, together with circumstantial data and morphological findings, especially in cases which have been in the water for less than 72 h [116][117][118][119][120][121][122][123].…”
Section: Electrolytessupporting
confidence: 57%
“…If antemortem findings are not available, vitreous sodium levels lower than 120 mmol/l could support the diagnosis of fatal hyponatremia [104]. Available clinical laboratory methodologies [122] VH vitreous humor, CSF cerebrospinal fluid, PF pericardial fluid, 3HB 3-β-hydroxybutyrate, HPLC high-performance liquid chromatography, EDTA ethylenediaminetetraacetic acid, HS-GC headspace-gas chromatography, GC-FID gas chromatography-flame ionization detector, GC-MS gas chromatography-mass spectrometry Vitreous potassium levels [1] are of no help in determining the potassium status of an individual immediately prior to death. Increased vitreous potassium levels have no diagnostic value, whereas low vitreous levels are theoretically indicative of hypokalemia.…”
Section: Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained concentrations of strontium in the ventricles and the differences in concentrations between the ventricles were not as high as the “typical drowning” definition of Azparren et al. However, they were within the cutoff ranges supporting the diagnosis of drowning, especially since the bodies had been recovered from seawater within 24 h .…”
Section: Discussionmentioning
confidence: 51%
“…Strontium was considered just as a supportive parameter for the diagnosis of drowning as many different factors reported in the literature can be effective on strontium concentrations. The obtained concentrations of strontium in the ventricles and the differences in concentrations between the ventricles were not as high as the "typical drowning" definition of Azparren et al However, they were within the cutoff ranges supporting the diagnosis of drowning, especially since the bodies had been recovered from seawater within 24 h (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 60%